2018
DOI: 10.1080/14643154.2018.1474330
|View full text |Cite
|
Sign up to set email alerts
|

Relations of social maturity, executive function, and self-efficacy among deaf university students

Abstract: This study explored possible associations of social maturity, executive function (EF), self-efficacy, and communication variables among deaf university students, both cochlear implant (CI) users and nonusers. Previous studies have demonstrated differences between deaf and hearing children and young adults in EF and EF-related social and cognitive functioning. EF differences also have been demonstrated between hearing children and deaf children who use CIs. Long-term influences of cochlear implantation in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Both first-order and second-order false belief tasks also involve sequential processing, as performance depends on recognition and retention of sequences of events. Several studies have suggested that hearing individuals generally outperform deaf individuals, both CI users and nonusers, on tasks requiring sequential processing, such as recall of sequentially-presented verbal or nonverbal information (Dawson, Busby, McKay, & Clark, 2002;Kronenberger et al, 2014;Marshall et al, 2015), although here again, findings are inconsistent (e.g., Edwards & Anderson, 2014;Marschark, Walton, Crowe, Borgna, & Kronenberger, 2018). The extent to which sequential processing skill is associated with performance on ToM tasks apparently has not been investigated previously with either deaf or hearing individuals.…”
Section: The Present Studymentioning
confidence: 78%
See 1 more Smart Citation
“…Both first-order and second-order false belief tasks also involve sequential processing, as performance depends on recognition and retention of sequences of events. Several studies have suggested that hearing individuals generally outperform deaf individuals, both CI users and nonusers, on tasks requiring sequential processing, such as recall of sequentially-presented verbal or nonverbal information (Dawson, Busby, McKay, & Clark, 2002;Kronenberger et al, 2014;Marshall et al, 2015), although here again, findings are inconsistent (e.g., Edwards & Anderson, 2014;Marschark, Walton, Crowe, Borgna, & Kronenberger, 2018). The extent to which sequential processing skill is associated with performance on ToM tasks apparently has not been investigated previously with either deaf or hearing individuals.…”
Section: The Present Studymentioning
confidence: 78%
“…While it may be that some aspects of social competency, such as social maturity and social confidence, do not differ between deaf young adults as a function of sign language or CI use (e.g., Antia & Kreimeyer, 2015;Marschark et al, 2017;Marschark, Walton, et al, 2018), these attributes may rely less on advanced cognitive skills than does ToM understanding. For social maturity and social confidence, the incidental learning from interactions with family, peers, and others to whom deaf children and young adults have had access may be sufficient to facilitate typically-developing social skills in early childhood, even if not at an equivalent pace to that of hearing peers.…”
Section: Discussionmentioning
confidence: 99%
“… Maki-Torkko et al, 2015 [ 105 ] Qualitative Sweden, hospital Survey post-CI between Nov 2008 and April 2011 Adults ≥ 18 years and unilateral implants between Feb 1992 and Jan 2010 (mean ± SD age = 66.0 ± 14.3 years, n = 101, men = 40 and women = 61). Marschark et al, 2018 [ 100 ] Cross-sectional USA, Rochester Institute of Technology (RIT) NR 115 with hearing loss (with CI = 49) and 80 hearing university students. Mertens et al, 2021 [ 61 ] Prospective cohort Australia, Belgium, Spain, Poland and UK, hospitals Test battery post-CI between April 2015 to August 2019 Older adults ≥ 55 years, mean ± SD age = 72 ± 7 years with CI (n = 24) and mean age = 73 ± 9 years without CI (n = 24).…”
Section: Resultsmentioning
confidence: 99%
“…There were positive improvements in social exchange such as being able to listen to significant others and having conversations with families or close friends. Marschark et al, 2018 [ 100 ] To examined relations among social maturity, executive function (EF), CI use, self-efficacy and communication skills among deaf university students. Executive function (cognitive and academic abilities) measured by the Learning, Executive, and Attention Functioning (LEAF) scale [ 126 , 127 ].…”
Section: Resultsmentioning
confidence: 99%
“…EF are a group of cognitive processes that enable voluntary control of our behaviors, thoughts and emotions (Marschark et al, 2018). They support reading comprehension beyond the linguistic skills that have been demonstrated to be relevant to reading in adolescents with TH (Sesma et al, 2009).…”
mentioning
confidence: 99%